189k views
5 votes
How to factorize the following expression?
pqr + pr + q + 1​

1 Answer

3 votes

Answer: (pr + 1)(q + 1)

===============================================

Work Shown:

Use the factor by grouping method to get the following.

pqr + pr + q + 1​

(pqr + pr) + (q + 1​)

pr(q + 1) + 1(q + 1)

(pr + 1)(q + 1)

We can use the FOIL rule, distribution, or the box method to expand out (pr+1)(q+1) to get the original expression again. This helps confirm the answer.

User Jong Shin
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.